Meningkatkan Kemampuan Berbahasa Melalui Permainan Bisik Berantai Anak Kelompok B Di RA Umdi Al-Ihsan Parepare - Novita Ashari; Syarifah Halifah; Ema Ainun Kholilah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
One very important indicator is language development because one of the factors that influence children's development in all aspects is children's language development, especially cognitive development. Language is a means of connecting and communicating children with the surrounding environment, so it can be concluded that language has an impact on the success of children in the future. Children's language development must be in accordance with the stages of the child's age. This study discusses language development, especially literacy in children aged 5-6 years. Where the focus of the research is so that children's language literacy can develop, for example, such as children being able to recognize the initial letters of names of objects. The method used is a series of whispering activities. Data collection techniques are carried out by observation, interviews, and documentation. Primary data sources come directly from teachers and students as many as 12 people. Based on the results of the chain whisper method research in improving language skills carried out at RA Umdi Al-ihsan Parepare showing a very good improvement.